An Inventory Model of Immediate and Delayed Delivery - Moinzadeh, Kamran; Ingene, Charles (Management Science, 1993)
This paper considers the long run, profit maximizing strategy of a distributor that holds a good (good 1) in inventory for immediate delivery and that offers a second good (good 2) for delayed delivery. When the two goods are substitutes, an out-of-stock situation for good 1 will cause some consumers (“walkers”) to seek the good elsewhere, other consumers (“waiters”) to accept a raincheck for later delivery of good 1, and others still (“switchers”) to place an order for good 2. It is shown that a profit maximizing strategy may entail setting a price for the delayed delivery item so as to encourage switching behavior. The rationale is that the distributor can hold a smaller inventory, thereby incurring lower holding costs, because out-of-stock situations are less costly than they would be without some consumers being willing to switch.